Polycentric development in China’s mega-city regions, 2001-08: A comparison of the Yangtze and Pearl River Deltas - Zhao, Miaoxi; Derudder, Ben; Huang, Junhao (DIE ERDE – Journal of the Geographical Society of Berlin, 2017)
Large-scale urban regions are increasingly functioning as the territorial backbone of the global economy. Many of these mega-city regions are polycentric in that they consist of a range of densely interwoven cities and towns. The purpose of this chapter is to analyse the geographies of these polycentric networks in what are arguably China’s two most important mega-city regions: the Yangtze River Delta (YRD) and the Pearl River Delta (PRD). To this end, we deployed a methodology that allowed the analysis of the shifting spatial organization of mega-city regions through the lens of the headquarters–branches linkages of corporations; that is, we explored the mega-city regions’ constituent urban networks by looking at the ownership linkages running from a corporation’s headquarters to the corporation’s branches. In the process, this research extended and refined the statistical tools that are often deployed to measure polycentricity. Our results suggest that in both the YRD and the PRD there are more and more linkages interconnecting the mega-city region. The two regions share the following features: the general level of polycentricity is increasing, even though the concentration of headquarters is also increasing; and the growth of the general level of polycentricity mainly originates from higher levels of network density. There are, however, also fundamental differences between the YRD and the PRD: firms in the PRD are more likely to set up branches beyond the prefectures’ boundaries, which results in higher levels of network density than in the YRD; there is a relatively ’flatter’ intercity network in the YRD compared to the PRD, in which there are more firms’ links interconnecting the four major cities (Guangzhou, Shenzhen, Dongguan and Foshan), rather than other small and medium-size cities.